2000
DOI: 10.1007/s005350050336
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic portal hypertension associated with systemic lupus erythematosus

Abstract: A case of idiopathic portal hypertension (IPH) associated with systemic lupus erythematosus (SLE) is reported in a 38-year-old man who had been diagnosed with SLE and treated for 18 years. Esophageal varices. found in 1994 on endoscopic examination, had been followed up for 2 years. On July 16, 1996, he was admitted to Nagoya University Hospital because there was a high risk of bleeding from the esophageal varices due to severe thrombocytopenia. As partial splenic embolization had temporarily controlled the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 12 publications
0
24
0
1
Order By: Relevance
“…However, it is widely accepted that autoimmune diseases (especially connective tissue diseases) increases the prevalence of IPH in certain patient groups. The most important IPH associated diseases are mixed connective tissue disease (6 cases [6] ), systemic sclerosis (20 cases [7] ) and systemic lupus erythematosus (16 cases [8] ). In addition, a Japanese survey [9] found that hypergammaglobulinemia is the most common presenting autoimmune dysfunction (26% of all included IPH patients), along with chronic thyroiditis as the most common autoimmune disease.…”
Section: Autoimmunity Theorymentioning
confidence: 99%
“…However, it is widely accepted that autoimmune diseases (especially connective tissue diseases) increases the prevalence of IPH in certain patient groups. The most important IPH associated diseases are mixed connective tissue disease (6 cases [6] ), systemic sclerosis (20 cases [7] ) and systemic lupus erythematosus (16 cases [8] ). In addition, a Japanese survey [9] found that hypergammaglobulinemia is the most common presenting autoimmune dysfunction (26% of all included IPH patients), along with chronic thyroiditis as the most common autoimmune disease.…”
Section: Autoimmunity Theorymentioning
confidence: 99%
“…In one fourth of the cases, esophageal varices are not completely eradicated after transabdominal devascularization procedure, and adjuvant endoscopic sclerotherapy can be performed afterwards with satisfactory results [14,15]. Some authors [15,19,32] support the idea of combining endoscopic treatment (EIS or EVL) with non-shunt operation for esophageal varices due to IPH. This case report demonstrates a complete eradication of varices after Hassab-Paquet procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The exact causes of IPH remain unclear, but some studies underlined a potential role of immunological abnormalities in these patients [1,31,32]. A large survey of IPH in Japan disclosed that 11.9% of cases were associated with one or two autoimmune diseases and 26.3% of them showed hypergammaglobulinemia [31].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, autoimmune disorders are frequently associated with IPH, such as systemic lupus erythematosus (LE) with positive LE cell phenomenon, 33,34 lupus anticoagulant, progressive systemic sclerosis, chronic thyroiditis, mixed connective tissue disease and Raynaud's phenomenon. [35][36][37] In fact, in this same issue of the Journal of Gastroenterology and Hepatology, two cases of IPH-associated scleroderma are described.…”
Section: See Article On Pagementioning
confidence: 99%